2020
DOI: 10.1101/2020.09.21.306415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tricarboxylic acid cycle and proton gradient inPandoravirus massiliensis: Is it still a virus?

Abstract: Since the discovery of Acanthamoeba polyphaga Mimivirus, the first giant virus of amoeba, the historical hallmarks defining a virus have been challenged. Giant virion sizes can reach up to 2.3 µm, making them visible by optical microscopy. They have large genomes of up to 2.5 Mb that encode proteins involved in the translation apparatus. Herein, we investigated possible energy production in Pandoravirus massiliensis, the largest of our giant virus collection. MitoTracker and TMRM mitochondrial membrane markers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…isolate has suggested that these enzymes have activity consistent with bioinformatic predictions, and that some are packaged into virions and would therefore influence host physiology soon after initial infection (57). Together with our results, this suggests that viral manipulation of central metabolic processes is a widespread mechanism employed by many Nucleocytoviricota, and that this is a common occurrence in viral infections in the ocean.…”
Section: Imitervirales (Fig 4 Fig S2) a Recent Study Of Tca Cycle Enzymes Encoded By A Pandoravirussupporting
confidence: 84%
See 1 more Smart Citation
“…isolate has suggested that these enzymes have activity consistent with bioinformatic predictions, and that some are packaged into virions and would therefore influence host physiology soon after initial infection (57). Together with our results, this suggests that viral manipulation of central metabolic processes is a widespread mechanism employed by many Nucleocytoviricota, and that this is a common occurrence in viral infections in the ocean.…”
Section: Imitervirales (Fig 4 Fig S2) a Recent Study Of Tca Cycle Enzymes Encoded By A Pandoravirussupporting
confidence: 84%
“…We detected expression of many of these central metabolic enzymes throughout the sampling period; genes involved in glycolysis, the TCA cycle, the pentose phosphate pathway, and beta oxidation were all present in the metatranscriptomes, and most were consistently expressed across timepoints, especially in Mimiviridae clades (Fig 4, Fig S2). A recent study of TCA cycle enzymes encoded by a Pandoravirus isolate has suggested that these enzymes have activity consistent with bioinformatic predictions, and that some are packaged into virions and would therefore influence host physiology soon after infection (54). Together with our results, this suggests that viral manipulation of central metabolic processes is a widespread mechanism employed by many Nucleocytoviricota , and that this is a common occurrence in viral infections in the ocean.…”
Section: Resultsmentioning
confidence: 84%
“…Giant viruses are viruses with a very large physical size (larger than some bacteria); they have a large genome compared to classical viruses (up to 1 to 2 megabases), as well as both types of nucleic acids. In addition, a recent study has shown that some giant viruses also have enzymes capable of producing energy (with the detection of the tricarboxylic acid cycle and proton gradient in Pandoravirus massiliensis) [ 75 ]. For this reason, only giant viruses were analyzed in this work.…”
Section: Genome Evolution and Mosaicism Representation: Rhizomes Constructionmentioning
confidence: 99%
“…Such control can be transcriptional regulation of nucleus- and mitochondrion-encoded genes related to energy metabolism, as in coccolithovirus [ 129 ]. Recently reported genome sequences of environmental MAGs [ 17 ] or isolated viruses even encode their own genes related to glycolysis, tricarboxylic acid cycle, succinate dehydrogenase, β-oxidation, and photosynthesis [ 17 , 77 , 81 , 101 ]. Genes encoding enzymes in cellular fermentation, such as pyruvate formate-lyase, have been found in Tetraselmis virus infecting green algae [ 73 ], which have anaerobic energy metabolism in low-oxygen condition [ 130 ].…”
Section: Functional Potential Of Virus-encoded Proteinsmentioning
confidence: 99%